Condition of 137Cs Activity in Karimunjawa Waters and its Distribution When an NPP Jepara is Operated - Muslim Muslim; Heny Suseno; Siti Saodah (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2016)
Karimunjawa islands are located in the middle of the Java Sea, approximately 83 km northwest of Jepara city. These islands have become an Indonesian marine tourism destination and since 2001 had been designated as a national park. The Indonesian government has chosen Muria peninsula in the district of Jepara, Indonesia as a site for a potential nuclear power plant (NPP). The purpose of this study was to determine the current level of radiocesium (137Cs) activity and forecast its spread if an NPP is operated at Jepara. To determine the distribution of 137Cs in Karimunjawa waters, a sampling of water was done in six stations. Simulation modeling was used to map the distribution of 137Cs should an NPP be constructed in Jepara. The results showed that 137Cs activity in Karimunjawa waters ranges from 0.12 to 0.39 mBq.L-1 with an average of 0.24 mBq.L-1. This value is slightly higher than previous studies in the coastal waters of Gresik, which had an average activity of 0.200 mBq.L-1 because the waters around Karimunjawa have a lower dilution rate than the coastal waters of Gresik. However, these values were considerably lower than those in the waters of Northeast Japan before the Fukushima nuclear power plant accident which registered 137Cs activity at 2-3 mBq.L-1.This indicates that 137Cs in Karimunjawa is not entirely from Fukushima rather from the global fallout. The 137Cs distribution model suggests that after 15 days, a leakage in the Muria Peninsula nuclear plant will not contaminate Karimunjawa waters because the current in the Java Sea is relatively weak and dominant in the westward direction. Thus, when an NPP leak only runs for 15 days, Karimunjawa waters remain safe.Keyword: 137Cs, Karimunjawa, NPP, modeling, Muria Peninsula